‘Those who can think, teach’: the pedagogical reasoning of pre-service teachers from different initial teacher education pathways - Langsford, Dale Heidi (My University, 2021)
South African initial teacher education (ITE) policy requires that all beginning teachers possess the same set of competences despite the variations in sequencing and pacing that exist between different qualification pathways (Department of Higher Education and Training, 2015, Appendix C). From the outset, beginner teachers are required to make decisions and judgements in their practice that requires the capacity to engage in pedagogical reasoning. This pedagogical reasoning is invisible and cannot be directly observed, even though it is a central and defining feature of professional teaching, but it can only be demonstrated in relation to a context of practice. Despite its central role in the practice of teaching, the literature on the pedagogical reasoning (particularly empirical studies) of pre-service and in-service teachers is scarce internationally, and entirely absent in the South African context. This study seeks to address this gap. The responses often participants (four fourth year Bachelor of Education (BEd) students, three Post Graduate Certificate in Education (PGCE) students, and three learnership student teachers) to their observations of a video recorded lesson formed the data set for this study. The study used concepts from Legitimation Code Theory (LCT; Maton, 2007) to show that the pedagogical reasoning of BEd participants demonstrated a significantly different semantic structure to that of those who had qualified by PGCE or Learnership routes. The findings of the data analysis suggest that when engaging in pedagogical reasoning, PGCE and Learnership participants tend to make axiological claims using everyday language and terminology, with little to no abstraction to principles of practice, using themselves as implicit models of exemplary practice as a basis for legitimation for their judgements. The BEd participants made more knowledge claims in their responses to the observation of a recorded lesson than the other cohorts. They used more specialised language and terminology which condensed more meaning to abstract principles or rules of teaching from the context of the lesson in the video that they observed. They also used both personal experiences of teaching and theoretical ideas as bases of legitimation. The interpretation of the data therefore indicates that the PGCE and Learnership participants predominantly employ a cultivated gaze to make judgements and engage in pedagogical reasoning from the outset of their careers, while the BEd participants drawn on both a cultivated gaze as well as a trained gaze. I argue, therefore, that the BEds drew on a wider field of criteria when engaged in pedagogical reasoning when responding to the recorded lesson. They were able to make sense of the teaching in the recorded lesson from the perspective of theory, and from the perspective of their own experiences where the criteria for good teaching are more explicit. The PGCE and Learnership participants drew from a single field of criteria, using their cultivated gaze, thereby limiting their criteria for good teaching and ways in which they could understand the teaching in the recorded lesson. The findings of this study show that differently qualified beginning teachers do not draw equally on experiential and conceptual tools when analysing an observed lesson. This may very well suggest that their responses to other artefacts of practice may be substantively different
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021